Indikator Proses Utama pada Proses Grinding dengan Pendekatan Manajemen Pengetahuan - Ikhwan Arief; Alfajri Nalda (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
This study discusses about key process indicators in grinding with the knowledge management approach. Common/key indicators used in the machine are workpiece, grinding wheel, dressing tool and coolant. The resulting key processeswill benefit firms and their operators especially new ones in managing scienceson grinding process that will allow knowledge transferred to new operators quickly. Process indicators are described with IDEF0 diagrams which will define the inputs, outputs, mechanisms and controls.